Perceptual Quality Model for Enhancing Telemedical Video Under Restricted Communication Channels - Schwering, Taralyn (My University, 2015)
Telemedicine has the potential to provide greatly increased access to medical training, consultation and care for individuals and populations located in remote regions of the Earth. In order for this to happen, telemedicine relies on delivery of high quality video over bandwidth limited internet connections. Methods of video encoding to accommodate these connections reduce the perceptual quality of telemedical video, reducing its clinical or educational impact. This thesis aims to understand how changes in bitrate, frame rate and frame size affect the perceptual quality of telemedical video through studies of objective and perceptual quality of two types of medical simulation video. H.264/AVC encoding was used to encode two medical simulation videos with varying bitrates, frame rates and frame sizes. Objective frame image quality tests and subjective video quality tests were performed on the resulting videos. It was observed that the objective frame image quality, as measured by the Structural Similarity (SSIM), is linearly related to the number of pixels per bit of the encoded video. It was also determined that perceptual quality of these videos was dependent primarily on the frame rate and frame image quality of the encoded video. Models are proposed from the results of each type of video showing how perceptual quality can be determined by the parameters chosen to encode a video (maximum bitrate, frame rate and frame size). The models proposed are unique for the type and purpose of video under investigation as well as the encoding method used. The models created will be useful to encode video for transmission over limited bandwidth networks while maintaining diagnostic and education quality.